Survey on incidence and severity of Stenocarpella macrospora (Earle) leaf blight of maize in the midaltitude zone of Nigeria - Olatinwo, R.O.; Deadman, M.L.; Cardwell, K.F.; Julian, A.M. (1999)
Surveys were conducted on the incidence and severity of Stenocarpella macrospora (Earle) Sutton (= Diplodia macrospora Earle) on maize in the mid-altitude zone of Nigeria in 1995 and 1996. The results indicated a possible link between disease severity and plant density. Fewer symptoms were observed at altitudes below 700m. There was no significant correlation between cropping system and incidence or severity.